Assessing Video Games to Improve Driving Skills: A Literature Review and Observational Study - Sue, Damian; Ray, Pradeep; Talaei-Khoei, Amir; Jonnagaddala, Jitendra; Vichitvanichphong, Suchada (JMIR Publications, 2014)
BackgroundFor individuals, especially older adults, playing video games is a promising tool for improving their driving skills. The ease of use, wide availability, and interactivity of gaming consoles make them an attractive simulation tool. ObjectiveThe objective of this study was to look at the feasibility and effects of installing video game consoles in the homes of individuals looking to improve their driving skills. MethodsA systematic literature review was conducted to assess the effect of playing video games on improving driving skills. An observatory study was performed to evaluate the feasibility of using an Xbox 360 Kinect console for improving driving skills. ResultsTwenty-nine articles, which discuss the implementation of video games in improving driving skills were found in literature. On our study, it was found the Xbox 360 with Kinect is capable of improving physical and mental activities. Xbox Video games were introduced to engage players in physical, visual and cognitive activities including endurance, postural sway, reaction time, eyesight, eye movement, attention and concentration, difficulties with orientation, and semantic fluency. However, manual dexterity, visuo-spatial perception and binocular vision could not be addressed by these games. It was observed that Xbox Kinect (by incorporating Kinect sensor facilities) combines physical, visual and cognitive engagement of players. These results were consistent with those from the literature review. ConclusionsFrom the research that has been carried out, we can conclude that video game consoles are a viable solution for improving user's physical and mental state. In future we propose to carry a thorough evaluation of the effects of video games on driving skills in elderly people.